Axial power distribution control in fast nuclear reactor based on proportional spatial-derivative method. (January 2021) - Yang, Minghan
Highlights: An axial power distributed control system for fast nuclear reactors is presented. The discretization process of the PSD controller is presented. The effectiveness of PSD method is verified in the semi-physical test platform. The PSD method provides simpler design and better dynamic performance than LPC. Abstract: Axial power distribution control is one of the key issues for Nuclear Power Plant (NPP) operation. In the most of NPPs, the axial power distribution control is realized by the Lumped Parameters Control (LPC) method, which often takes the axial power difference between adjacent nodes as the controlled object. However, the nuclear reactor core has a typical distributed parameters feature. With the number of discrete nodes increases, the control system design is more and more complex. Therefore, it is necessary to develop the Distributed Parameter Control (DPC) method. In this work, a DPC method based on the Proportional Spatial-Derivative (PSD) controller is presented. Experiments show that the power distribution control system based on the PSD control method can inhibit the power peak. Meanwhile, the comparison between the PSD and PID controllers shows that the DPC system based on the PSD method has better dynamic performance than LPC system.